Ultrasound characteristics, serum biochemistry and outcome of ectopic pregnancies presenting during COVID‐19 pandemic. (1st December 2021) - Kyriacou, C.; Cooper, N.; Robinson, E.; Parker, N.; Barcroft, J.; Kundu, S.; Letchworth, P.; Sur, S.; Gould, D.; Stalder, C.; Bourne, T.
ABSTRACT: Objective: To describe and compare the characteristics of ectopic pregnancies (EPs) in the year prior to vs during the coronavirus disease 2019 (COVID‐19) pandemic. Methods: This was a retrospective analysis of women diagnosed with an EP on transvaginal sonography conducted at a center in London, UK, providing early‐pregnancy assessment, between 1 January 2019 and 31 December 2020. Women were identified via the Astraia ultrasound reporting system using coded and non‐coded outcomes of EP or pregnancy outside the uterine cavity. Data related to predefined outcomes were collected using Astraia and Cerner electronic reporting systems. Main outcome measures included clinical, ultrasound and biochemical features of EP, in addition to reported complications and management. Results: There were 22 683 consultations over the 2‐year period. Following consultation, a similar number and proportion of EPs were diagnosed in 2019 (141/12 657 (1%)) and 2020 (134/10 026 (1%)). Both cohorts were comparable in age, ethnicity, weight and method of conception. Gestational age at the first transvaginal sonography scan and at diagnosis were similar, and no difference in location, size or morphology of EP was found between the two cohorts. Serum human chorionic gonadotropin (hCG) levels at the time of EP diagnosis were higher in 2020 than in 2019 (1005 IU/L vs 665 IU/L; P  = 0.03). The proportions of women according to type of final EP management were similar, but the rate of failed first‐line management was higher during vs before the pandemic (16% vs 6%; P  = 0.01). The rates of blood detected in the pelvis (hemoperitoneum) on ultrasound (23% vs 26%; P  = 0.58) and of ruptured EP confirmed surgically (9% vs 3%; P  = 0.07) were similar in 2019 vs 2020. Conclusions: No difference was observed in the location, size, morphology or gestational age at the first ultrasound examination or at diagnosis of EP between women diagnosed before vs during the COVID‐19 pandemic. Complication rates and final management strategy were also unchanged. However, hCG levels and the failure rate of first‐line conservative management measures were higher during the pandemic. Our findings suggest that women continued to access appropriate care for EP during the COVID‐19 pandemic, with no evidence of diagnostic delay or an increase in adverse outcome in our population. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.